Systematic Literature Review : Apakah Media Pembelajaran Mampu Mempengaruhi Hasil Belajar Matematika - Lilik Muji Hastutik; Kusmiyati Kusmiyati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
One of the tools that can help students learn better is learning media. This study aims to determine how the use of learning media affects students' mathematics learning outcomes. The data used in this research were collected from relevant journals. This study employed the Systematic Literature Review (SLR) method. Researchers utilized the Google Scholar database and the Publish or Perish application to gather nationally accredited journal articles from Sinta 1 to 4. The results indicate that the use of learning media in mathematics instruction has a significant impact on students' interest, motivation, and learning outcomes.